Analisis Hukum Acara Mahkamah Konstitusi: Implikasi Putusan terhadap Penegakan Hak Asasi Manusia - Alarode Lahoya Simbolon; Sidi Ahyar Wiraguna (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The Constitutional Court of Indonesia is a judicial institution with the authority to review laws against the 1945 Constitution of the Republic of Indonesia, resolve disputes between state institutions, decide on the dissolution of political parties, and adjudicate election result disputes. In exercising its authority, the Constitutional Court functions not only as the guardian of the constitution but also as a protector of human rights. This article aims to analyze how the procedural law of the Constitutional Court, as regulated under Law Number 24 of 2003 and its amendments, serves as a crucial instrument to ensure fair, transparent, and accountable proceedings in cases involving constitutional rights. This study adopts a normative juridical approach by examining legislation, legal doctrines, and Constitutional Court decisions that have had a significant impact on the protection of human rights. The analysis reveals that several rulings of the Court have expanded interpretations of human rights, although challenges remain regarding the consistency of procedural application and the effectiveness of decision enforcement. Therefore, strengthening the procedural law of the Constitutional Court is essential for ensuring the substantive and sustainable protection of human rights in Indonesia.